The development of a sense of control scale - Dong, Mia Y.; Sandberg, Kristian; Bibby, Bo M.; Pedersen, Michael N.; Overgaard, Morten (Frontiers in Psychology, 2015)
In the past decades, sense of control – the feeling that one is in control of one’s actions has gained much scientific interests. Various scales have been used to measure sense of control in previous studies, yet no study has allowed participants to create a scale for rating their control experiences despite advances in the neighbouring field of conscious vision has been linked to this approach. Here, we examined how participants preferred to rate sense of control during a simple motor control task by asking them to create a scale to be used to describe their sense of control experience during the task. Scale with 6 steps was most frequently created. Even though some variability was observed in the number of preferred scale steps, descriptions were highly similar across all participants when scales were converted to the same continuum. When we divided participants into groups based on their number of preferred scale steps, mean task performance and sense of control could be described as sigmoid functions of the noise level, and the function parameters were equivalent across groups. We also showed that task performance increased exponentially as a function of control rating, and that, again, function parameters were equivalent for all groups. In summary, the present study established a participant-generated 6-point sense of control rating scale for simple computerized motor control tasks that can be empirically tested against other measures of control in future studies.